Legume (Mimosoideae) fossil woods from the late Miocene (Salicas Formation) of northwestern Argentina - Pujana, Roberto Roman (2014)
Six pieces of fossil wood from the late Miocene of Northwestern Argentina (Salicas Formation) are described. They are all assigned to Prosopisinoxylon anciborae Martínez based on the presence of the following diagnostic characters: vessels of two distinct diameter classes, simple perforation plates, vestured pits, abundant axial parenchyma and wide rays. Signiﬁ cant anatomical variation exists among specimens but they are regarded as a single taxonomic unit because usually a gradual transition is observed among most variable characters. A principal component analysis (PCA) was performed and results agree with the taxonomic placement. The analysis also shows discrete clusters of other related Leguminosae fossilgenera. Wood anatomy suggests a warm and dry climate for the zone supporting previous studies.